If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(15 + -7x) = 0 (15 * -1 + -7x * -1) = 0 (-15 + 7x) = 0 Solving -15 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 7x = 0 + 15 7x = 0 + 15 Combine like terms: 0 + 15 = 15 7x = 15 Divide each side by '7'. x = 2.142857143 Simplifying x = 2.142857143
| -8=3b+45 | | 180-74=x | | -2[5w-7]+9=-7 | | -9+22=m-2 | | 5x+14=38-3x | | 6(1-3)=3(-4m+6) | | 3d+3=18-2d | | 529-(8+1)= | | 6(x-2)=3(x) | | 4x+15+2x=6(x+4) | | -5(3-q)+4=5q+11 | | -4(1+7x)-3=7(-6x-3) | | 0.5x-3=0.75x-7.75 | | 5q^4-405=0 | | 5m+3=3(m-3) | | s^3-g^3= | | 8(2x+8)=3x+9 | | 4x-10=-2-4x | | 2(x+7)=2x+9 | | -8(-7-3a)=2(7a+8) | | 5+4(-2)=2(t+7)+1 | | 8(3x+8)=3x+9 | | 2r-22=-22+6r | | 11d+9d-2=5a+22 | | 2(5r-8)-5r=4(r-4)+8 | | 24+2x=4x | | -2+15=12x-5-11x | | 18n+7=21 | | 11x+9x=18 | | G(0)=x-5 | | 3=-2(-y+6) | | 6(x+2)=3(x+7) |